Changes in Respiratory Muscle Thickness during Mechanical Ventilation: Focus on Expiratory Muscles. (May 2021) - Shi, Zhong-Hua; de Vries, Heder; de Grooth, Harm-Jan; Jonkman, Annemijn H.; Zhang, Yingrui; Haaksma, Mark; van de Ven, Peter M.; de Man, Angelique A. M. E.; Girbes, Armand; Tuinman, Pieter R.; Zhou, Jian-Xin; Ottenheijm, Coen; et al.
Abstract : Background: The lateral abdominal wall muscles are recruited with active expiration, as may occur with high breathing effort, inspiratory muscle weakness, or pulmonary hyperinflation. The effects of critical illness and mechanical ventilation on these muscles are unknown. This study aimed to assess the reproducibility of expiratory muscle ( i.e., lateral abdominal wall muscles and rectus abdominis muscle) ultrasound and the impact of tidal volume on expiratory muscle thickness, to evaluate changes in expiratory muscle thickness during mechanical ventilation, and to compare this to changes in diaphragm thickness. Methods: Two raters assessed the interrater and intrarater reproducibility of expiratory muscle ultrasound (n = 30) and the effect of delivered tidal volume on expiratory muscle thickness (n = 10). Changes in the thickness of the expiratory muscles and the diaphragm were assessed in 77 patients with at least two serial ultrasound measurements in the first week of mechanical ventilation. Results: The reproducibility of the measurements was excellent (interrater intraclass correlation coefficient: 0.994 [95% CI, 0.987 to 0.997]; intrarater intraclass correlation coefficient: 0.992 [95% CI, 0.957 to 0.998]). Expiratory muscle thickness decreased by 3.0 ± 1.7% (mean ± SD) with tidal volumes of 481 ± 64 ml ( P < 0.001). The thickness of the expiratory muscles remained stable in 51 of 77 (66%), decreased in 17 of 77 (22%), and increased in 9 of 77 (12%) patients. Reduced thickness resulted from loss of muscular tissue, whereas increased thickness mainly resulted from increased interparietal fasciae thickness. Changes in thickness of the expiratory muscles were not associated with changes in the thickness of the diaphragm ( R 2 = 0.013; P = 0.332). Conclusions: Thickness measurement of the expiratory muscles by ultrasound has excellent reproducibility. Changes in the thickness of the expiratory muscles occurred in 34% of patients and were unrelated to changes in diaphragm thickness. Increased expiratory muscle thickness resulted from increased thickness of the fasciae. Abstract : Inter- and intrarater reproducibility was strong (intraclass correlation coefficients 0.994 [95% CI, 0.987 to 0.997] and 0.992 [95% CI, 0.957 to 0.998], respectively). Muscle thickness increased by 3.2% after increasing lung volume by a mean of 481 ± 64 ml. Although muscle thickness remained stable in the majority of subjects, it decreased in 22% and increased in 12% with no association with changes in diaphragmatic thickness. Exploratory analyses suggest no relation with a variety of clinical or physiologic parameters or medications. Time-dependent decreases in thickness resulted from muscle loss, whereas increases largely resulted from increases in thickness of the interparietal fasciae.Supplemental Digital Content is available in the text.